1983
DOI: 10.1172/jci110773
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a carboxyterminal peptide fragment of the human choriogonadotropin beta-subunit excreted in the urine of a woman with choriocarcinoma.

Abstract: A B S T R A C T We have observed low-molecular weight carboxyterminal fragments of the human choriogonadotropin (hCG) a-subunit in the urines of several women with choriocarcinoma, and we have characterized one fragment in detail. Its apparent molecular weight by gel chromatography on Sephadex G-100 was 14,200. The fragment was not adsorbed to concanavalin A-Sepharose, indicating that it lacked the asparagine-linked carbohydrate groups of intact hCG#. It was active in radioimmunoassays (RIA) using antisera eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Standardizing assays that measure heterogeneous mixtures is difficult, and is probably impossible on theoretical grounds [56,57]. The only fully satisfactory solution will be to determine the principal components of such mixtures [58].…”
Section: Discussionmentioning
confidence: 99%
“…Standardizing assays that measure heterogeneous mixtures is difficult, and is probably impossible on theoretical grounds [56,57]. The only fully satisfactory solution will be to determine the principal components of such mixtures [58].…”
Section: Discussionmentioning
confidence: 99%
“…Because such fragments were not usually found in the sera, they have been considered to be urinary products. Amr et al (5,23) have shown that carboxy-terminal peptide fragments of the hCGjfl were commonly contained in the urine of patients with gestational trophoblastic neoplasia but rarely in the urine of pregnant women and suggested that it could be accounted for by the metabolism of the forms of hCG that bear an altered carbohydrate structure. In this regard, interestingly, we have already found that all the c-hCG samples, including the same samples studied here, contain the unusual multiantennary complex-type sugar chains which are not found in normal pregnancy hCG (6).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these works suggested that the carbohydrate structures of hCG change by neoplastic transformation of trophoblast (1)(2)(3). On the other hand, several investigators have reported the presence of low molecular weight hCG/3-related fragments in urine of patients with trophoblastic neoplasms (4,5). We found that definite structural changes commonly occurred in the sugar chains of choriocarcinoma urine hCG samples (6), and also observed that the same samples bearing such unusual carbohydrates released an unusual fragment, in addition to aand 0-subunits, when subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) under reducing conditions with dithiothreitol (DTT) (7).…”
mentioning
confidence: 99%
“…When the ratio of Ag-2 to Ag-1 was compared in urinary hCG preparations from various patients, it was found that the ratio was very low in normal pregnancy but increased in hydatidiform mole and was the highest in choriocarcinoma. In recent studies, Masure et al (1981) and Amr et al (1983) also showed the presence of small immunoreactive hCG molecules in urine from patients with hCG-secreting neo¬ plasmas and choriocarcinomas, respectively. The latter authors proved that the small hCG compo¬ nents were hCG-ß carboxy-terminal fragments.…”
mentioning
confidence: 92%